Evolutionary inspired approach for mental stress detection using EEG signal. (1st July 2022) - Sharma, Lakhan Dev; Bohat, Vijay Kumar; Habib, Maria; Al-Zoubi, Ala' M.; Faris, Hossam; Aljarah, Ibrahim
Abstract: Stress is a pensive issue in our competitive world and it has a huge impact on physical and mental health. Severe health issues may arise due to long exposure of stress. Hence, its timed detection can be helpful in managing stress periods. In this regard, electroencephalogram (EEG) based techniques have been widely explored, as stress severely impact the functioning and structure of brain. These non-invasive methods for stress detection need improvement in terms of predictive accuracy and reliability. In this work, a novel approach for stress detection has been presented using short duration of EEG signal. Entropy based features were extracted from EEG signal decomposed using stationary wavelet transform. Selected features were used for classification using different supervised machine learning algorithms. Further, different evolutionary inspired approaches were deployed to optimize the parameters of support vector machines (SVM) and perform feature weighting, simultaneously. SVM optimized using whale optimization algorithm resulted in an accuracy of 97.2559%. Accurate detection using short duration EEG signal shows potential of this technique for timed and reliable detection of stress. Highlights: Stationary Wavelet Transformed based signal decomposition. Entropy based feature extraction. WOA has been utilized for optimizing parameters of SVM and to perform feature weighting. Better classification rate for stress detection.